Effects on RCS of a perfect electromagnetic conductor sphere in the presence of anisotropic plasma layer. Issue 1 (2nd January 2018) - Ghaffar, A.; Hussan, M. M.; Illahi, A.; Alkanhal, Majeed A. S.; Ur Rehman, Sajjad; Naz, M. Y.
Abstract: Effects on RCS of perfect electromagnetic conductor (PEMC) sphere by coating with anisotropic plasma layer are studied in this paper. The incident, scattered and transmitted electromagnetic fields are expanded in term of spherical vector wave functions using extended classical theory of scattering. Co and cross-polarized scattered field coefficients are obtained at the interface of free space-anisotropic plasma and at anisotropic plasma-PEMC sphere core by scattering matrices method. The presented analytical expressions are general for any perfect conducting sphere (PMC, PEC, or PEMC) with general anisotropic/isotropic material coatings that include plasma and metamaterials. The behavior of the forward and backscattered radar cross section of PEMC sphere with the variation of the magnetic field strength, incident frequency, plasma density, and effective collision frequency for the co-polarized and the cross polarized fields are investigated. It is also observed from the obtained results that anisotropic layer on PEMC sphere shows reciprocal behavior as compared to isotopic plasma layer on PEMC sphere. The comparisons of the numerical results of the presented analytical expressions with available results of some special cases show the correctness of the analysis.